A PRAGMATIC STUDY ON MEME COMICS - Febrian Dwi Harystiani; Yuli Widiana (Humaniora Scientia, 2018)
This research is a pragmatic study which discusses speech acts in Meme Comics. The source ofdata is facebook of Meme Comics. This research applied the descriptive method. The kinds ofspeech acts in Meme Comics are classified intoÂ  representatives, directives, commisives,expressives, and declaratives. Expressives speech acts is the most frequently found. Then, theleast speech acts which are found are commissives speech acts. Furthermore, the functions ofrepresentative speech acts contain of the act of asserting and concluding. Meanwhile, there aresome functions in directives such as to order and to request. In commissives, there are somefunctions which are found such as to promise and to offer. The functions in expressives are toexpress anger, shock, dissapointment, amazement, suspicion, and insinuation. Next, there aresome functions in declaratives such as to confirm and to declare. The most frequently functionsof speech acts are the act of asserting and the least functions of speech act are the act ofexpressing suspicion, amazement, and confirmation. The kinds of speech acts are used toexpress the satire and sarcasm about everyday life in Meme Comics.Keyword: Pragmatics, Speech Acts, Meme Comics